Potential role of exercise echocardiography and right heart catheterization in the detection of early pulmonary vascular disease in patients with systemic sclerosis. Issue 3 (October 2019) - Kovacs, Gabor; Olschewski, Horst
Pulmonary vascular disease represents one of the most frequent complications in systemic sclerosis leading to increased mortality. The recognition and appropriate clinical management of early pulmonary vascular disease could significantly improve the prognosis of affected patients. Early pulmonary vascular disease is characterized by the histological signs of pulmonary vascular remodeling, mildly increased mean pulmonary arterial pressure (21–24 mmHg) at rest, abnormal pulmonary hemodynamics during exercise, decreased exercise capacity, and a high risk for development of pulmonary arterial hypertension. Pulmonary hemodynamics can be investigated during exercise by echocardiography or by right heart catheterization both representing important clinical tools for the screening and confirmation of early pulmonary vascular disease. Further studies are needed to better understand the clinical course of systemic sclerosis patients with early pulmonary vascular disease and to define the characteristics of patients that will or will not profit from pulmonary arterial hypertension treatment.